Analysis of 8th Grade Students’ English Speaking Difficulties and Teaching Strategies After Covid-19 Pandemic - Purwananda, I Gede Arda; Padmadewi, Ni Nyoman; Kadek Sintya Dewi (International Journal of Language and Literature, 2023)
This study was motivated by the difficulties experienced by students in speaking English after the Covid-19 pandemic, as well as the efforts of teachers in overcoming these difficulties. The main objectives of this study were to identify the difficulties faced by students in speaking English and explore the strategies implemented by teachers to overcome them. This study used a qualitative approach with observation and interview methods as primary data collection techniques. The subjects of the study consisted of 31 students of grade 8A and an English teacher. Data analysis was conducted descriptively. The results showed that the main difficulties of students in speaking English included lack of vocabulary, low levels of focus, and nervousness. To overcome these difficulties, teachers have implemented two main strategies: first, giving students time to read and understand English sentences and vocabulary; second, using visual media such as images and videos, and presenting native speakers directly. These strategies have proven effective in increasing students' focus during the learning process. The implications of this study indicate the importance of utilizing adaptive learning strategies in overcoming obstacles in English learning, especially in the post-pandemic context.